2018
DOI: 10.1002/etep.2563
|View full text |Cite
|
Sign up to set email alerts
|

Parameter uncertainty in the optimal coordination of overcurrent relays

Abstract: Summary Generally, the relay coordination problem is solved without considering parameter uncertainties, while uncertainties in the line parameters and current transformer ratios make the fault current passing through the overcurrent relay inaccurate and could cause the miscoordination. To overcome this drawback, in this paper, a novel method based on interval analysis is introduced to model parameter uncertainties in the coordination problem. Considering parameter uncertainties, the coordination constraints a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Generally, the protected line's impedance values are determined through calculations in which the soil resistivity, towers and conductor heights, conductors' transpositions, towers geometry, and spacing between consecutive towers are assumed as constants. However, these assumptions introduce uncertainties and errors to the actual line's parameters in practical cases [36].…”
Section: Uncertainties and Errors In Line Parametersmentioning
confidence: 99%
“…Generally, the protected line's impedance values are determined through calculations in which the soil resistivity, towers and conductor heights, conductors' transpositions, towers geometry, and spacing between consecutive towers are assumed as constants. However, these assumptions introduce uncertainties and errors to the actual line's parameters in practical cases [36].…”
Section: Uncertainties and Errors In Line Parametersmentioning
confidence: 99%
“…The operating time t of a directional overcurrent relay is an inverse function of the short-circuit current [50]. The equation that models the operation of the numerical inverse time overcurrent relay is defined by two parameters, i.e ; the delay time TDS or the delay factor TMS, the value of TMS usually varies between 0.1 to 1.1 s [51] and the pickup current Ip, which is the minimum current value above which the relay will start to operate [52]. This function has two constants, A represents the constant for the relay characteristics and B represents the inverse time type, which are defined as 0.14 and 0.02 respectively [53], [54].…”
Section: Relay Characteristicsmentioning
confidence: 99%
“…The second case study implemented is IEEE 30-bus system that consists of 76 overcurrent relays as shown in figure 5 [36]. The streamlined TDS values are appeared table 6 and the result has been compared with the literature.…”
Section: B Ieee 30-bus Systemmentioning
confidence: 99%
“…In reference [28], adaptive protection coordination scheme using numerical directional overcurrent relays. In [29]- [36] Optimal Coordination of DOCRs had been implemented Using different optimizers. In [37] the problem of DOCRs in a power system is handled with the firefly algorithm (FA).…”
Section: Introductionmentioning
confidence: 99%